HUBUNGAN KONDISI SOSIAL EKONOMI PETERNAK SAPI TERHADAP KESADARAN LINGKUNGAN DI KECAMATAN MUSUK DAN KECAMATAN TAMANSARI KABUPATEN BOYOLALI TAHUN 2019 - Pertiwi, Shenina Putri; Muryani, Chatarina; Utomowati, Rahning (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2022)
This study aims to (1) analyze the socio-economic conditions of cattle farmers in Musuk Village, Sukorejo Village, and Jemowo Village, (2) Analyze the level of environmental awareness in processing cattle waste in Musuk Village, Sukorejo Village, and Jemowo Village, and (3 ) Analyzing the relationship between socio-economic conditions and environmental awareness in processing cattle waste in Musuk Village, Sukorejo Village, and Jemowo Village. The research method used in this study is a mixed qualitative and quantitative method using a spatial approach, with the research population being households whose heads of families work as cattle breeders. The results of this study are (1) the socio-economic classification of cattle breeders in Musuk Village, Sukorejo Village, and Jemowo Village is low. (2) Cattle farmers in Musuk Village, Sukorejo Village, and Musuk Village have a moderate level of environmental awareness. (3) Socio-economic conditions of cattle farmers in Musuk Village, Sukorejo Village, and Jemowo Village influence environmental awareness in processing livestock waste, but it is less significant.